Arquitetura contemporânea em madeira: um ensaio a partir de (ins)urgências tecnológicas e socioambientais - Prado, Louise da Mata Oliveira (2020)
Timber, one of the oldest and most traditional building materials in the history of architecture, has lost a lot of space in the industrial culture developed in modernist architecture and in consumer culture that has expanded along with postmodern architecture. It is believed, in general, that the new role of this material as a construction system was associated with the urgency of renewable practices in response to the intensive depletion of Earth’s natural resources, especially at the end of the twentieth century. From the perception of different contemporary movements and theories at the service of architecture, it is noted that the interest in the use of timber has also been revived in current trajectories such as ecological architecture, low-tech, eco-tech, high-tech, “more for less” architecture, critical regionalism, architecture “more for less ”, biophilia and phenomenology. Taking as its basis the period between the 90's and nowadays, this work has as its general objective to study the timber architectural works in the light of contemporary production in different realities, systematizing them by their narratives according to the Theories of Architecture. In the form of a theoretical essay, the methods and techniques used consist of a literature search, whose analysis was carried out in a descriptive and reflective way from the contemporary urgencies that lead the evolution of timber architecture in the current production, contemplating ethical, technological issues, interferences in local technical cultures, social activism and atmospheres caused by multisensory perception in the built space.